Genetic variants and magnetic resonance imaging measures in multiple sclerosis: a systematic review - Nowak, Jan Krzysztof; Guzikowska-Ruszkowska, Izabela; Łopaciuch, Jadwiga; Jankowska, Wiesława; Piotrowska, Ewa; Dziedzic-Szeszuła, Ewa; Kapecka, Kinga; Walkowiak, Jarosław (Journal of Medical Science, 2016)
Introduction. Although environmental factors play the major role in the etiopathogenesis of multiple sclerosis (MS), genetic factors are implicated as well. We aimed to summarize the current knowledge on the relationship between genetic variants and magnetic resonance (MR) imaging measures in MS. Material and Methods. A systematic review. In December 2016, Scopus (since the year 1980; including MEDLINE) was searched for studies meeting predefined criteria designed to identify articles regarding: multiple sclerosis, genetic variants, and MR imaging. These were then analyzed to identify publications linking polymorphisms and MR findings. Results. The search yielded 290 items; 26 were included in the final analysis. Two genome-wide association studies (GWAS) and two projects employing panels of a few dozen of genes of interest provided most of the data. The other publications concerned no more than 5 genes at a time. Twenty studies reported positive findings. The relationship between HLA-DRB1*15:01 or BDNF rs6265 (Val66Met) and the radiologic course of MS was not consistent across the studies. An intersection of the results of the two GWAS yielded: OPCML (rs11223055), PTPRD (rs1953594), and WWOX (rs11150140, rs1116525) (brain atrophy) as well as CDH13 (rs692612) and PLCB1 (rs6118257) (lesion load). Conclusions. Genetic variants were shown to correlate with MS-related brain atrophy and lesion load. Further research in the field is required.